BroadGAN: Generative adversarial networks of discriminating separate features based on broad learning. (March 2022) - Jin, Qimin; Lin, Rongheng; Yang, Fangchun
Abstract: Since the generative adversarial network (GAN) was proposed in 2014, it has rapidly become a hot topic in the field of deep learning. In recent years, there are many optimizations for GAN, which are divided into three kinds, including the optimization of loss functions, external structure of network and internal structure of network. Few people optimizes GAN from internal structure of network, and because of the process of game, slow training speed is one of the biggest problems of GAN. This paper introduces the ideology of broad learning algorithm (Chen and Liu, 2017) to put forward the multi-judge generative adversarial network method based on different random features to enhance the quality of generative result and increase the training speed of GAN (Goodfellow et al., 2014). This model provides a method which reduce the input information of each discriminator to optimize the training process of GAN. The experiments on cifar10 and anime face dataset find that our model obtains a better performance than the GMAN model and Base model. This paper finds a group of hyper-parameters to enhance the BroadGAN.